Thailand Financial Sector Assessment Program : Funded Pension System - World Bank; International Monetary Fund (World Bank, Washington, DC, 2019)
While Thailand’s pension system is typically described as a multipillar pension scheme, its design is highly fragmented and offers adequate coverage only to a small segment of the population, including civil servants and high-income individuals. In its 2018 Article IV report, the IMF highlighted the need for a broader pension reform, including parametric changes and ender inclusivepolicies to improve female labor force participation and attenuate the impact of aging on productivity growth. While these reforms are needed, private pensions can also play a role inimproving retirement income for individuals. As agreed with the Thai authorities, this technical note provides an assessment of the private, funded components of the pension system. A key component assessed is the voluntary provident fund scheme (PVD). The PVD scheme is voluntary and operates as a tax-incentivized scheme, which allows both employers and employees to take advantage of generous tax benefits for savings for retirement. This note also addresses the challenges of the private, funded system and proposes policy recommendations for increasing coverage, improving efficiency, and delivering sustainable retirement income in the payout phase. This note is organized as follows. The next section provides a brief description of the current overall pension system, public and private; Section III provides a diagnostic of the main challenges in the private, funded system; and Section IV provides recommendations for optimizing the design of the private, funded pension system. The focus of the note is to improve the incentive structure of the private, funded pension scheme.